1984
DOI: 10.1152/ajpheart.1984.247.1.h124
|View full text |Cite
|
Sign up to set email alerts
|

Elastase, collagenase, and the biaxial elastic properties of dog carotid artery

Abstract: Segments of dog carotid artery were studied in vitro at four longitudinal extension ratios, lambda z = 1.2, 1.4, 1.6, and 1.8, in randomized order. At each length, the pressure was elevated in steps to 200 mmHg or until the vessels buckled. Vessels were studied under control conditions and after treatment with moderate doses of degradative enzymes: 80 U/ml elastase for 90 min or 640 U/ml collagenase for 120 min. These doses were selected, following pilot studies, to degrade vessels but not to destroy them. Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
66
1
3

Year Published

1985
1985
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 0 publications
9
66
1
3
Order By: Relevance
“…Dobrin and coworkers found that there was no change in axial compliance with collagenase treatment, contradicting the results of this study [49,50]. However Gundiah et al found collagenase treatment affected wall compliance in both directions, which supports the findings here [18].…”
Section: Collagenase Treatmentcontrasting
confidence: 81%
“…Dobrin and coworkers found that there was no change in axial compliance with collagenase treatment, contradicting the results of this study [49,50]. However Gundiah et al found collagenase treatment affected wall compliance in both directions, which supports the findings here [18].…”
Section: Collagenase Treatmentcontrasting
confidence: 81%
“…It is generally accepted that under conditions of low wall strain, elastin is the primary load-bearing component of the vascular wall and that as wall strain increases collagen plays a more prominent role in supporting passive wall tension (1,8,16). For example, Dobrin and Canfield (16) examined the passive biaxial mechanical behavior of dog carotid arteries following treatment with elastase or collagenase.…”
Section: Functional Relevance Of Relaxin-induced Vascular Wall Remodementioning
confidence: 99%
“…These data are therefore helpful to develop the SEF of different wall constituents. Among models with selectively altered constituents, elastase-treated arteries offer an attractive model to access the biomechanical properties of arteries after elastin degradation, as seen in pathologies such as aortic stiffening with age and aneurysm formation (Dobrin 1989;Dobrin and Canfield 1984;Hayashi et al 1987). Recently, Fonck et al studied the collagen engagement profile in intact and elastase-treated arteries by applying the SEF proposed by Zulliger et al on P-r o curves and suggested a clear interaction between collagen and elastin in the arterial wall (Fonck et al 2007).…”
Section: Elastin 3d Ultrastructure In Arteriesmentioning
confidence: 99%